Josephson effect in point contacts between "f -wave" superconductors - Mahmoodi, R.; Kolesnichenko, Yu.A.; Shevchenko, S.N. (Физика низких температур, 2002)
A stationary Josephson effect in point contacts between triplet superconductors is analyzed theoretically for most probable models of the order parameter in UPt₃ and Sr₂RuO₄. The consequence of misorientation of crystals in the superconducting banks on this effect is considered. We show that different models for the order parameter lead to quit different current-phase relations. For certain angles of misorientation a boundary between superconductors can generate a spontaneous current parallel to the surface. In a number of cases the state with a zero Josephson current and minimum of the free energy corresponds to a spontaneous phase difference. This phase difference depends on the misorientation angle and may possess any value. We conclude that experimental investigations of the current-phase relations of small junctions can be used for determination of the order parameter symmetry in the superconductors mentioned above.